Identifying and facing the lack of discipline to manage EFL classrooms in a public context in Colombia with sixth graders. (2016)
The project was based on identifying and facing the lack of discipline problems in EFL classrooms in a public context in Colombia with sixth graders; it was focused in a group of students between 11 and 13 years old. This is collaborative-action research, taking into account this method the researchers interviewed and trained the teacher, observed classes and with the help of the trained teacher, there were implemented some strategies. The results of this investigation suggests that with the implementation of different strategies students can improve their discipline inside the classroom.